INTEGRASI PENDIDIKAN KARAKTER BERBASIS MULTIKULTURAL DALAM PEMBELAJARAN PAI DI SD 2 YAYASAN PUPUK KALTIM KOTA BONTANG - Pramana, Dimas Dery; Fauzan, Umar (Pascasarjana PAI Multikultural Universitas Yudharta Pasuruan, 2024)
Elementary schools play a crucial role in shaping students' character through Islamic Religious Education (PAI) that integrates multicultural values, creating a young generation that values diversity and supports a harmonious and inclusive school environment. This study, conducted at SD 2 Yayasan Pupuk Kaltim, aims to examine how the integration of character values in PAI is applied to shape students' character. This qualitative research draws data from interviews with the school principal and PAI teachers, using interviews, observations, and documentation for data collection, and employs interactive techniques for data analysis. The study shows that the curriculum is designed to include values such as tolerance, mutual respect, and togetherness by aligning teaching materials and methods that reflect cultural diversity in Indonesia. The positive impacts of implementing multicultural character education integration include increased tolerance, critical thinking skills, social awareness, and students' academic achievement.